1998
DOI: 10.1016/s0896-6273(00)80445-6
|View full text |Cite
|
Sign up to set email alerts
|

Auto Transplants for Parkinson's Disease?

Abstract: 94080 in the globus pallidus (pallidotomy) have been tried. Pallidotomy was practiced prior to the development of The Disease L-DOPA, discarded, and recently regained acceptance Parkinson's disease is the third most common neurode- (Lang et al., 1997). The rationale behind pallidotomy is generative disorder, with a prevalence of approximately easy to understand. Since in the absence of dopaminer-1% of the population over 65. Affected individuals suffer gic inputs the globus pallidus is hyperactive, selective f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…However, unequivocal evidence for GDNF expression in CB of adult rodents was obtained from heterozygous knock-out GDNF/lacZ mice, in which the cells expressing GDNF contain ␤-galactosidase deposits that can be labeled with the characteristic blue X-gal staining . Using this experimental tool, we compared the level of GDNF expression in the CB and that in the AM, SCG, or retina, which are catecholaminergic donor tissues used in transplantation studies to treat PD in animals and humans (Bohn et al, 1987;Itakura et al, 1988;Yurek and Sladek, 1990;Rosenthal, 1998). The histological illustrations in Figure 1 clearly show the high level of GDNF expression in the CB (blue-green color deposits in A) and its complete absence in the AM (C, D), SCG (E, F ), and retina (G, H ).…”
Section: Resultsmentioning
confidence: 99%
“…However, unequivocal evidence for GDNF expression in CB of adult rodents was obtained from heterozygous knock-out GDNF/lacZ mice, in which the cells expressing GDNF contain ␤-galactosidase deposits that can be labeled with the characteristic blue X-gal staining . Using this experimental tool, we compared the level of GDNF expression in the CB and that in the AM, SCG, or retina, which are catecholaminergic donor tissues used in transplantation studies to treat PD in animals and humans (Bohn et al, 1987;Itakura et al, 1988;Yurek and Sladek, 1990;Rosenthal, 1998). The histological illustrations in Figure 1 clearly show the high level of GDNF expression in the CB (blue-green color deposits in A) and its complete absence in the AM (C, D), SCG (E, F ), and retina (G, H ).…”
Section: Resultsmentioning
confidence: 99%
“…Fetal human mesencephalic cells (which include dopaminergic neural stem cells) were the first cells to be transplanted in an attempt to cure Parkinson's disease (Rosenthal 1998). When injected into the striatum of Parkinson's patients, they differentiate into dopaminergic neurons (DANs) and make synaptic connections with host neurons, restoring the activity of the striatopallidothalamic output pathway toward normal.…”
Section: Central Nervous Systemmentioning
confidence: 99%
“…Functional replacement of specific neuronal populations through transplantation of neural tissue represents an attractive therapeutic strategy for treating neurodegenerative disorders such as Parkinson's disease 1 . Recent advances in neural stem cell biology have shown that multipotent neural progenitors can be isolated, expanded, and used as source material for brain transplants [1][2][3][4][5][6][7][8] .…”
mentioning
confidence: 99%